Modelado y caracterización del proceso de temple - Saldaña Celis, Daniel Roberto (2023)
In the present investigation, the modeling and characterization of the tempering heat treatment is carried out. The methodology to carry out consisted of starting with the definition of the tempering parameters and then they are introduced to the elaborated model, later it was corroborated with a commercial software and a final contrast was obtained in charge of the laboratory tests. As a result, it was obtained that the data obtained from the articles served for the mathematical model and the temperature curves Id the cooling curves were obtained. In addition, the microconstituents were obtained in each of the points of the test tube, which were contracted with the mechanical properties of said material. In this way it was possible to corroborate the effect of the mathematical model and its usefulness.